ANALISIS PENGELOLAAN BARANG MILIK DAERAH PADA PEMERINTAH DAERAH KABUPATEN ACEH TENGAH - Ropida Rezeki Utami; Aliamin Aliamin; Heru Fahlevi (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2019)
A fixed aset is one of the elements that must be managed well in order to produce reliable information in the financial statements of the local government office. The purpose of this study is to analyze the suitability between the implementation of the management of local property in the Central Aceh District with the regulation of Ministry of Home Affairs (Permendagri), No. 17 of 2008 and identify the constraints encountered in the management of local property in the district of Central Aceh. Using the qualitative method, the study finds that the management of  local property in the district of Central Aceh in 2015 has been in line with the Permendagri, No. 17 of 2008, but in its implementation there have been many shortcomings due to non-supportive of human resources, facilities and infrastructure, and the leaderships. Thus, this study suggest the government apparatus, especially those who are in charges of management of local property enhance their ability by attending education, training, and technical workshops in the field of financial management of local government, aiming towards professional human resources. Keywords: Aset Management, Regional Property  Abstrak Aset tetap merupakan salah satu unsur yang harus dikelola dengan baik agar menghasilkan informasi yang andal dalam laporan keuangan daerah. Tujuan penelitian ini yaitu untuk menganalisis kesesuaian antara implementasi pengelolaan barang milik daerah di Kabupaten Aceh Tengah dengan Peraturan Menteri dalam Negeri Nomor 17 Tahun 2007 dan mengidentifikasi kendala-kendala yang ditemui dalam pengelolaan barang milik daerah di Kabupaten Aceh Tengah. Desain penelitian ini menggunakan metode kualitatif -deskriptif. Hasil penelitian menunjukkan bahwa pengelolaan barang milik daerah Kabupaten Aceh Tengah pada tahun 2015 masih mengacu pada permendagri nomor 17 tahun 2008, namun pada pelaksanaannya masih banyak kekurangan karena tidak didukung dengan sumber daya manusia, sarana dan prasarana dan dukungan dari atasan. Penelitian ini merekomendasikan kepadaSumber Daya Manusia, khususnya aparatur kerja di di bidang pengelolaan barang milik daerah untuk mengikuti pendidikan, pelatihan dan bimbingan teknis di bidang pengelolaan keuangan daerah agar terwujud SDM yang professional.